CALCIUM ANTAGONISTS IN THE TREATMENT OF ARTERIAL HYPERTENSION DURING PREGNANCY - R. I. Striuk (Рациональная фармакотерапия в кардиологии, 2016)
According to WHO data, arterial hypertension (HT) is revealed in 15-20% of pregnant women. In different regions of Russia the incidence of pregnancy HT varies from 7 to 29%. In women with HT started before pregnancy , perinatal losses are observed in 3, 8%, premature births – in 15, 3% and intrauterine growth retardation - in 16, 6%. Physiological gestational changes of hemodynamics are described. Hypertensive pregnant patients of high and low risk are defined. Non-pharmacological treatment of pregnant women with HT is presented in details. Antihypertensive therapy may not be used in hypertensive patients of low risk with blood pressure (BP) of 140-160\90-110 mm Hg. If BP is higher antihypertensive therapy should be used immediately. Dihydropyridine calcium antagonists (CA) is drugs of choice for HT treatment during pregnancy , especially “advanced” CA of the third generation. They have predictable efficacy. It is possible to use short-acting nifedipine for treatment of acute HT in pregnant patients.